L’attuazione del Protocollo di Madrid da parte dell’Italia ed il rispetto di altri obblighi internazionali convenzionali - VIGNI, PATRIZIA (GIUFFRE', 2001)
Italy is a State party to the Antarctic Treaty. Italy is also party to several international treaties concerning matters of interest for Antarctica. One must ascertain if Italy must recognise some relevance of the other international treaties when it is enforcing the norms of the Antarctic Treaty system. Which rules must be applied? Are there some norms that must prevail over others?